1997
DOI: 10.1002/1521-3951(199712)204:2<685::aid-pssb685>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Composition Dependence of Exciton Peak Positions and Band Gap Energies of Zn1?xMgx(?0.19Se Epitaxial Films

Abstract: The temperature dependence of the 1s exciton energy has been measured in Zn1—xMgxSe epitaxial films at compositions x = 0, 0.07, 0.12, and 0.19 from 2 K up to 280 K. Detailed numerical fits of the individual temperature dependences are provided on the basis of an analytical four‐parameter representation developed recently by one of the authors. These are compared with previously used three‐parameter models of Viña et al. and Varshni. The x‐dependence of the exciton energy, E1s(T, x), and of the fundamental ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Instead, according to [50], one has to endow the data points in question with weighting factors which are inversely proportional to the square of the corresponding error bars (cf. [23] and [32]). This means, for the data constellation in consideration, a reduction of the weight for the E g (T !…”
Section: Analyses and Results For Iii±v Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, according to [50], one has to endow the data points in question with weighting factors which are inversely proportional to the square of the corresponding error bars (cf. [23] and [32]). This means, for the data constellation in consideration, a reduction of the weight for the E g (T !…”
Section: Analyses and Results For Iii±v Compoundsmentioning
confidence: 99%
“…In analogy to most gallium-and indium-based III±V compounds, a considerable variety of E g (T) and E gx (T) data sets has been published during the past three decades also for II±VI compounds (for a list of references see [31,32]). The majority of these data sets, however, can be readily seen to be rather scarce, rather restricted (usually to T 300 K) and/or relatively inaccurate, so that they appear more or less insufficient for a trustworthy determination of empirical parameter sets (independently of the analytical model used).…”
Section: Analyses and Results For Ii±vi Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very common that Varshni parameters fall in a broad range for the same material. This could be attributed to the empirical origin of Varshni relation [18,19]. Manoogian and Woolley [15] have suggested that after removing the contribution of the thermal expansion of lattice, the b parameter follows the…”
Section: Resultsmentioning
confidence: 99%